Conceptualization of a Multicultural Islamic Religious Education Curriculum Implementation Model in a Multiethnic Society - Muhammad Ilham Hidayat; M. Syahrul (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Multiethnic society is a social reality inseparable from the life of the Indonesian nation and demands an educational approach that is sensitive to diversity. Islamic Religious Education (PAI) has a strategic role in instilling moderate, inclusive, and socially harmonious Islamic values. However, the implementation of the PAI curriculum so far has tended to be normative-doctrinal and has not fully accommodated multicultural values ​​systematically. This study aims to examine and conceptualize a model for implementing a multicultural Islamic Religious Education curriculum in a multiethnic society. The research uses a qualitative approach with a type of library research through analysis of books, scientific journal articles, and relevant educational policy documents. Data were analyzed using content analysis techniques with stages of classification, reduction, interpretation, and conceptual synthesis. The results of the research show that the implementation of a multicultural PAI curriculum can be conceptualized through four main components, namely curriculum planning based on multicultural values, dialogical and participatory learning implementation, holistic evaluation including cognitive, affective, and behavioral aspects, and strengthening an inclusive educational culture. This conceptual model affirms that the multicultural PAI curriculum functions as an instrument of character education and social transformation that is relevant in building tolerant, moderate, and civilized attitudes in the midst of a multiethnic society. This research is expected to be a theoretical reference for the development and implementation of a PAI curriculum that is responsive to socio-cultural diversity.